All-fiber tribo-ferroelectric synergistic electronics with high thermal-moisture stability and comfortability - Yang, Weifeng; Gong, Wei; Hou, Chengyi; Su, Yun; Guo, Yinben; Zhang, Wei; Li, Yaogang; Zhang, Qinghong; Wang, Hongzhi (Nature communications, 2019)
Developing fabric-based electronics with good wearability is undoubtedly an urgent demand for wearable technologies. Although the state-of-the-art fabric-based wearable devices have shown unique advantages in the field of e-textiles, further efforts should be made before achieving “electronic clothing” due to the hard challenge of optimally unifying both promising electrical performance and comfortability in single device. Here, we report an all-fiber tribo-ferroelectric synergistic e-textile with outstanding thermal-moisture comfortability. Owing to a tribo-ferroelectric synergistic effect introduced by ferroelectric polymer nanofibers, the maximum peak power density of the e-textile reaches 5.2 W m −2 under low frequency motion, which is 7 times that of the state-of-the-art breathable triboelectric textiles. Electronic nanofiber materials form hierarchical networks in the e-textile hence lead to moisture wicking, which contributes to outstanding thermal-moisture comfortability of the e-textile. The all-fiber electronics is reliable in complicated real-life situation. Therefore, it is an idea prototypical example for electronic clothing. Though triboelectric technology is attractive for designing next-generation electronic textiles, current devices do not meet performance requirements. Here, the authors report all-fiber e-textiles featuring a triboelectric/ferroelectric synergistic effect for optimizing performance and wearability.